Pengembangan Permainan Rintangan Harta Karun Terhadap Gerak Motorik Kasar dalam Pembelajaran PJOK untuk Siswa Sekolah Dasar - Jauza'a Friji Fadinar Setiono; Drastiana Siwi Maheswari (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to develop the “Treasure Hunt Obstacle” game in Physical Education, Sports, and Health (PJOK) learning to improve elementary school students’ gross motor skills. This study employed a Research and Development (R&D) method using the ADDIE development model consisting of analyze, design, develop, implement, and evaluate stages. The research subjects consisted of elementary school students involved in small-scale and large-scale trials. Data collection techniques included observation, media expert validation questionnaires, learning expert validation questionnaires, and student response questionnaires. Before implementation, the student response instrument was tested for validity and reliability. The validity test results indicated that all instrument items were declared valid in both small-scale and large-scale trials, while the reliability test obtained a Cronbach Alpha value of 0.88, categorized as highly reliable. The media expert validation achieved a percentage of 90%, categorized as feasible, while learning experts obtained an average percentage of 92.50%, also categorized as feasible. Student responses in the small-scale trial reached 92.6%, while the large-scale trial reached 84.1%, with an average score of 88.35%, categorized as very good. The implementation results showed that the “Treasure Hunt Obstacle” game was able to increase students’ activeness, enthusiasm, and gross motor skills in PJOK learning. Therefore, the developed game is feasible to be used as a PJOK learning model in elementary schools. Keywords: ADDIE, Elementary School, Game, Gross Motor Skills, Physical Education